Synthesis, characterization and molecular dynamics simulation of dendronized poly(3,5-diphthalimidoalkylphenyl methacrylate)s - Alvarado, N.; Alegría, L.; Sandoval, C.; Gargallo, L.; Leiva, A.; Radic, D. (Polimery, 2021)
Dendronized methacrylates containing 3,5-diphthalimidoalkylphenyl moieties (with ethyl, propyl or butyl spacer groups) were synthesized. These monomers were then polymerized using radical polymerization. Monomers and polymers were characterized using Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance methods (1H NMR and 13C NMR). Molecular weight was estimated by multi-angle static light scattering (MALS). Molecular dynamics simulation was performed to evaluate the conformational radius of gyration (Rg) and the end-to-end distance (ree). Different spatial arrangements depending on the length of the spacer group are observed.